1998
DOI: 10.1007/bf02831348
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high risk pregnancies with relation to ABO haemolytic disease of newborn

Abstract: IgM and IgG anti A and anti B antibody status of 100 antenatal O group mothers (who had non O group husbands) were studied. Of these, 3 mothers had an IgM anti A antibody levels ranging from 1:512 to 1:2048 and IgG ranging from 1:1204 to 1:2048, IgM anti B ranging from 1:128 to 1:512 and IgG anti B ranging from 1:256 to 1:512. All these mothers had A + ve children and all these children suffered from ABO haemolytic disease of newborn (HDN). A 4th mother had an IgM anti A titre of 1:64 and IgG anti A titre of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
1
6
1
Order By: Relevance
“…8 In an investigation carried out in Kerala, KC Usha and PV Sulochana had observed a direct correlation between high titres of IgM and IgG anti-A or anti-B levels and occurrence of ABO HDFN. 9 In our study titre of maternal antibody in ABO HDFN was positively correlated with grades of DAT, risk related to peak bilirubin levels, severity of disease and intensity of treatment and was negatively correlated with cord blood haemoglobin levels. A direct correlation between high titres of IgM and IgG anti-A or anti-B levels and ABO HDFN was observed by KC Usha and Sulochana.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…8 In an investigation carried out in Kerala, KC Usha and PV Sulochana had observed a direct correlation between high titres of IgM and IgG anti-A or anti-B levels and occurrence of ABO HDFN. 9 In our study titre of maternal antibody in ABO HDFN was positively correlated with grades of DAT, risk related to peak bilirubin levels, severity of disease and intensity of treatment and was negatively correlated with cord blood haemoglobin levels. A direct correlation between high titres of IgM and IgG anti-A or anti-B levels and ABO HDFN was observed by KC Usha and Sulochana.…”
Section: Resultssupporting
confidence: 51%
“…A direct correlation between high titres of IgM and IgG anti-A or anti-B levels and ABO HDFN was observed by KC Usha and Sulochana. 9 But in contrast to above-mentioned findings, Grundbacher et al and Marsh et al had opined that there existed a poor quantitative relationship between maternal antibody levels and the ensuing haemolytic process, which was attributed to variations in the strength and reactivity of ABO antigens among infants. 10,11 Chan Shu observed that there was no difference between group A and group B infants in the frequency and severity of haemolytic disease.…”
Section: Resultsmentioning
confidence: 91%
“…In another study by Usha and Sulochana. [6] including 100 antenatal O group mothers, ABO-HDFN was encountered in three neonates with high titers of both IgG and IgM anti-A and anti-B antibodies. In our three cases of ABO-HDFN, BET was required due to severe hyperbilirubinemia (>20 mg/dl) in the first 72 h of life.…”
Section: Discussionmentioning
confidence: 99%
“…ABO incompatibility occurs in 15-20% of all pregnancies, which produces hemolytic disease in 10% of these cases [2]. High serum bilirubin levels due to hemolysis of red blood cells secondary to transplacental passage of antibodies lead to increased risk of bilirubin encephalopathy and kernicterus at bilirubin levels lower than that of jaundiced newborns without active hemolysis.…”
Section: Introductionmentioning
confidence: 99%